Vohwinkel syndrome, ichthyosiform variant - by Camisa - Case report - Liliam Dalla Corte; Mariana Vale Scribel da Silva; Carina Flores de Oliveira; Gerson Vetoratto; Raquel Bissacotti Steglich; Josiane Borges (Sociedade Brasileira de Dermatologia, 2013)
Vohwinkel syndrome or keratoderma hereditaria mutilans is a rare autosomal dominant palmoplantar keratosis, which manifests in infants and becomes more evident in adulthood. Its mode of inheritance is autosomal dominant with mutation in loricrin and Connexin 26 genes. Patients with this mutation present hyperkeratosis of the palms and soles, constricting bands of the digits, usually on the fifth, and starfish-shaped hyperkeratosis on the dorsal aspects of the hands and feet. The disease mostly occurs in white women, where constricting fibrous bands appear on the digits and can lead to progressive strangulation and auto-amputation (pseudo-ain-hum).The authors report a rare case of a patient with a clinical ichthyosiform variant of Vohwinkel syndrome.